2014
DOI: 10.1186/1556-276x-9-43
|View full text |Cite
|
Sign up to set email alerts
|

Surface chemistry of SnO2 nanowires on Ag-catalyst-covered Si substrate studied using XPS and TDS methods

Abstract: In this paper we investigate the surface chemistry, including surface contaminations, of SnO2 nanowires deposited on Ag-covered Si substrate by vapor phase deposition (VPD), thanks to x-ray photoelectron spectroscopy (XPS) in combination with thermal desorption spectroscopy (TDS). Air-exposed SnO2 nanowires are slightly non-stoichiometric, and a huge amount of C contaminations is observed at their surface. After the thermal physical desorption (TPD) process, SnO2 nanowires become almost stoichiometric without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 26 publications
(27 reference statements)
0
28
3
Order By: Relevance
“…This conclusion is opposite to our recent experience, as the presence of Ag catalyst was not observed in VPD SnO2 nanowires deposited on Ag-covered Si(100) substrate [9].…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…This conclusion is opposite to our recent experience, as the presence of Ag catalyst was not observed in VPD SnO2 nanowires deposited on Ag-covered Si(100) substrate [9].…”
Section: Resultscontrasting
confidence: 99%
“…Relying on the SEM (Figure 1) as well as XPS results before and after TDS procedure ( Figure 2), it can be concluded that the gold particles can be covered by the carbon and the bonding between them impedes removing C contaminations during the TDS process. This is a limitation that has not been observed in the case of the previously studied Ag -covered Si(100) substrate [9].…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Quantitative analysis of the surface chemistry of SnO 2 films was based on the area (intensity) of the main core level XPS O1s, Sn3d, and C1s, weighted by the corresponding atomic sensitivity factor (ASF) and showed that SnO 2 is slightly non-stoichiometric with an [O]/[Sn] ratio of 1.7-1.8. This value is typical for nanostructured metal oxides [41], which have oxygen vacancy defects in the surface region of the SnO 2 grains. XPS measurements also revealed that carbon is the main surface contaminant of the SnO 2 grains.…”
Section: Xps Of the Sno 2 :Au Filmsmentioning
confidence: 97%